1. PENGARUH METODE EKSTRAKSI TERHADAP AKTIVITAS PENANGKAL RADIKAL BEBAS EKSTRAK METANOL KULIT BIJI PINANG YAKI (Areca vestiaria Giseke) - Mokoginta, Eka Pratiwi (PHARMACON, 2013)
This research to determine the effect of extraction method on free-radical scavengers on shellof yaki pinang fruit. Yaki betel nut shell extraction is done by the method of maceration,percolation and soxhletasi. Activity test done with free-radical scavengers DPPH. Resultmethod were analyzed by using UV-Vis spectrophotometer. Results of research on methodsoxhletasi have free-radical scavengers that activity is quite high in concentrations of 50mg/L (85,16%) and 100 mg/L (92,31%) compared to the maceration extraction method thathas a value of percent inhibition of 74,61% at a concentration 50 mg/L and 81,32% at aconcentration of 100 mg/L and percolation to the value of 14,28% at a concertration of 50mg/L, and 17,17% at a concentration of 100 mg/L using the DPPH test.Key words : pinang yaki (Areca vestiaria Giseke, antioxidant, DPPH